2017
DOI: 10.1155/2017/2483652
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic and Cytotoxicity LQB 123 Profile: Safety and Tripanocidal Effect of a Phenyl-t-Butylnitrone Derivative

Abstract: The therapeutic options for Chagas disease are limited and its treatment presents a number of drawbacks including toxicity, drug resistance, and insufficient effectiveness against the chronic stage of the disease. Therefore, new therapeutical options are mandatory. In the present work, we evaluated the effect of a phenyl-tert-butylnitrone (PBN) derivate, LQB 123, against Trypanosoma cruzi forms. LQB 123 presented a trypanocidal effect against bloodstream trypomastigotes (IC50 = 259.4 ± 6.1 μM) and intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…LQB303 reduced the number of both the extracellular and intracellular amastigotes of T. cruzi in vitro, and this inhibitory effect on parasite growth was irreversible. Recently, another PBN derivative, LQB123 showed trypanocidal activity against the intracellular amastigotes and other clinically relevant forms of the parasite (Cupello et al, 2017). When comparing the IC 50 /48 h for amastigotes incubated with LQB123 (188 μM) with parasites challenged with LQB303 (3 μM), we observed that LQB303 was 63 times more active than LQB123.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…LQB303 reduced the number of both the extracellular and intracellular amastigotes of T. cruzi in vitro, and this inhibitory effect on parasite growth was irreversible. Recently, another PBN derivative, LQB123 showed trypanocidal activity against the intracellular amastigotes and other clinically relevant forms of the parasite (Cupello et al, 2017). When comparing the IC 50 /48 h for amastigotes incubated with LQB123 (188 μM) with parasites challenged with LQB303 (3 μM), we observed that LQB303 was 63 times more active than LQB123.…”
Section: Discussionmentioning
confidence: 90%
“…However, mice treated with PBN alone did not show decreased parasite persistence (Wen et al, 2010). Modifications to the PBN molecule increases its trypanocidal effect, as seen with the PBN derivative, LQB123, which demonstrates trypanocidal effects on the proliferative and infective forms of T. cruzi, as well as low cytotoxicity to mammalian cells (Cupello et al, 2017).…”
Section: Introductionmentioning
confidence: 98%